Penerapan Metode Problem Based Learning (PBL) dalam Kurikulum Merdeka - Muhamad Irgi Abdillah Az-zarkasyi; Hindun Hindun (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2024)
Problem Based Learning (PBL) is a learning method applied by teachers aimed at training students' high-level thinking skills. The education system in Indonesia has experienced eleven curriculum changes, starting from 1947 until now. This research will discuss the application of the PBL method to the independent curriculum. The aim of this research is to determine the results of applying the PBL method in aspects of the independent curriculum. The method used in this research is a descriptive qualitative method, this method can describe how educators will implement it with students during teaching and learning activities. The research results related to the application of the PBL problem based learning method in the independent curriculum include several aspects of the independent curriculum, namely basic learning, teaching skills, group targeting, and the use of technology.